Guide of evaluation of clinical competences in the fourth year of Dentistry - Odalys Martín Reyes; Neisy Fernández Carmenates; Lourdes García Vitar; Odalys Bravo Cano (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2019)
The learning evaluation is at the moment debate center and all the actors' of an University concern and it constitutes a feedback for its management, it is for that reason that the creation and improvement of evaluative instruments with the purpose of establishing uniform approaches that diminish the influence of the subjective factor in the qualifications in the teaching learning process, for that it was carried out a bibliographical revision from November 2017 to March 2018 and methodological workshop with the professors of the community of fourth year of the Faculty of Odontology with the objective of proposing an observation guide for the evaluation of clinical competences in dentistry that unifies the approaches evaluative in the final exam of the subjects Integral attention to the Family II and III, being constituted this instrument with all the necessary elements to evaluate each student's acting and this way to elevate the quality of the evaluative process in the fourth year of the career.